Effectiveness of music therapy in children with autism spectrum disorder: A systematic review and meta-analysis - Ke, Xiaohua; Song, Wei; Yang, Minguang; Li, Jianhong; Liu, Weilin (Frontiers in Psychiatry, 2022)
Objectives: This study was to investigated the efficacy of music therapy (MT) in children with autism spectrum disorder (ASD) via a meta-analysis that comprehensively evaluated data from all eligible research in this field. Design: Systematic review and meta-analysis. Setting: A systematic search of the PubMed, Embase, and Cochrane Library databases from inception to October 2021 to identify studies that administered MT to children with ASD. Results: Eight randomized controlled trials (RCTs) including 608 participants met the inclusion criteria. The meta-analysis showed that MT was associated with a significant increase in social reactions among children with ASD (standardized mean difference (SMD) = 0.24, 95% confidence interval (CI) [0.03,0.46], I2 = 0%, P = 0.03). However, MT did not elicit a significant increase in symptom severity (SMD = 0.17, 95% CI [-0.04,0.38], I2 = 0%,P = 0.12), social adaptive behavior (SMD = 0.02, 95% CI [-0.44,0.48], I2 = 0%,P = 0.93) or speech (SMD = 0.04, 95% CI [-0.39, 0.47], I2 = 0%, P = 0.86) in children with ASD. Conclusions: MT can improve social skills in children with ASD; however, there does not seem to be a consensus on the persistence of its effects. These findings can inform clinical practice. Promoting the use of MT in children with ASD and improving its symptoms are the ultimate goals.